Development of Cotton Irrigation Based on Computer Technology - Matyakubov B. Sh.; Karabayev A.; Zakirova S. Kh.; Urinov A. A.; Diyorova M. X.; Davronov Q. A. (BIO Web of Conferences)
This study examines the critical intersection of global climate change and increasing water scarcity, with a particular focus on developing optimized irrigation practices for cotton production in the Andijan region. Using the CropWat software, guided by the Food and Agriculture Organization (FAO) methodology, we conducted a comprehensive analysis of local soil and hydrogeological conditions to formulate evidence-based irrigation strategies. The results show that seasonal irrigation requirements for cotton vary significantly across hydromodular regions, ranging from 3000 m³/ha in the dry season (IX) to 5900 m³/ha in the rainy season (I). Moreover, our findings highlight the importance of adapting irrigation practices to regional climate and soil characteristics to improve water use efficiency. By implementing these evidence-based irrigation regimes, we aim to not only improve cotton yields but also contribute to sustainable water management practices in the context of a rapidly changing climate. This study highlights the need for adaptive agricultural practices and provides a basis for further research on irrigation optimization, ultimately supporting agricultural sustainability and food security in water-stressed regions. Future research will also examine the integration of alternative irrigation technologies and their potential impact on optimizing water use in cotton production.